Integrated Life Cycle Cost Comparison and Environment Impact Analysis of the Concrete and Asphalt Roads. (2022) - Kumari, Madhuri; Gupta, Prakash; Deshwal, Sahil Singh
Abstract: India is leveraging ingenious inventions to execute the most complex road projects in a timely and eco-friendly manner, with the additional advantage of lower project life-cycle costs. Massive road infrastructure development in the country would yield a multiplier effect on development. Life Cycle Cost Analysis (LCCA) is an important method to properly control the expenditure on the construction and maintenance of infrastructure system. It assists in figuring out a cost-effective technology to adopt during the design period of a project for a feasible pavement design. This study is an attempt to perform a detailed life-cycle cost analysis of concrete and asphalt roads. Also, the Environmental Impact Analysis (EIA) of concrete and bitumen roads are performed in terms of Green House Gases (GHGs) emissions. A 30-year analysis period is adopted for performing LCCA per km length of concrete and bitumen pavements. The Net Present Value (NPV) method is used for calculating the life-cycle cost. EIA is carried out during various phases such as raw materials sourcing, manufacturing of dense bituminous macadam and concrete, laying and maintenance of roads. The results show that the concrete roads are 20% economical than the bitumen roads in terms of LCCA carried out for a 30-year analysis period. Also, the bitumen pavement entails more energy during per year period than concrete pavement. The study of life-cycle cost indicates that the maintenance and user costs of concrete pavement are much lower as compared to bitumen pavement. LCCA and EIA study indicates that the concrete pavements may be given preference over bitumen pavements as it offers dual advantage of lowering environmental impact by reducing the volume of construction materials and lower maintenance costs with long life span.